2012
DOI: 10.1002/jbm.a.34080
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblast response to puerarin‐loaded porous titanium surfaces: An in vitro study

Abstract: Recent studies demonstrate puerarin stimulates bone formation, suggesting its potential application in dental implantology field. The aim of this study was to investigate effects of puerarin-loaded titanium surfaces on the promotion of osteogenesis in preosteoblasts (MC3T3-E1). Puerarin was prepared onto titanium surfaces with varying concentration (10(-9) M, 10(-8) M, 10(-7) M, and 10(-6) M) by biomimetic calcium phosphate deposition process. Surface characteristics were performed by field-emission scanning e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 74 publications
3
8
0
Order By: Relevance
“…In the present study, NO production and the anabolic effect of puerarin on hBMSCs were simultaneously blocked by ICI182780, an estrogen receptor (ER) antagonist, suggesting that puerarin exerts its function through ERs and that the NOS-NO pathway may include downstream effectors of the ER. These findings are consistent with other studies showing the stimulatory effects of puerarin on the osteoblastic cell line MC3T3-E1, which were also blocked by tamoxifen, another anti-estrogen reagent (38).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, NO production and the anabolic effect of puerarin on hBMSCs were simultaneously blocked by ICI182780, an estrogen receptor (ER) antagonist, suggesting that puerarin exerts its function through ERs and that the NOS-NO pathway may include downstream effectors of the ER. These findings are consistent with other studies showing the stimulatory effects of puerarin on the osteoblastic cell line MC3T3-E1, which were also blocked by tamoxifen, another anti-estrogen reagent (38).…”
Section: Discussionsupporting
confidence: 93%
“…34 Yang et al reported that biomimetic calcium phosphate coating of titanium promoted accelerated ALP activity at 4, 7, and 14 days and OC production at 14 days. 35 These studies support the results of the present study, which indicated that the chemical properties of HAp itself accelerated the differentiation of bone marrow stromal cells (BMSCs) into osteoblasts. Osteoblasts can migrate and attach to HAp rapidly, supporting marrow stromal cell differentiation into osteoblasts.…”
Section: Discussionsupporting
confidence: 90%
“…Zhou et al reported that three‐dimensional (3D) Sr 1 ‐HAp nanorods might provide an excellent environment that promotes messenger ribonucleic acid (mRNA) of Runx2, ALP activity, and expression of OP and OC at 7 and 14 days . Yang et al reported that biomimetic calcium phosphate coating of titanium promoted accelerated ALP activity at 4, 7, and 14 days and OC production at 14 days …”
Section: Discussionmentioning
confidence: 99%
“…Puerarin‐loaded titanium surfaces elevated pre‐osteoblasts differentiation in MC3T3‐E1 cells (Yang et al ., ). Puerarin could increase the amount of calcium nodules in umbilical cord mesenchymal stem cells (MSCs), accelerate differentiation of MSCs into osteoblasts, and promote MSC proliferation (Cai et al ., ).…”
Section: Pharmacological Actionsmentioning
confidence: 97%